Language demography - Moreno Fernández, Francisco (Routledge, Taylor & Francis Group, 2024)
Demography and demolinguistics -- Linguistics for demographers -- Demography for linguists -- Demolinguistic data and sources -- Demolinguistic factors -- Demolinguistic analyses -- Applications of demolinguistics.
Keywords: Linguistik; Demographie